2
$\begingroup$

I have an inequality problem which is as follow:

If $a,b,c$ are positive integers, with $a^2+b^2-ab=c^2$ prove that $(a-b)(b-c)\le0$.

I am not so good in inequalities. So, please give me some hints so that I can proceed.

Thanks.

$\endgroup$
2
9
$\begingroup$

It is a nice example of how an algebraic inequality can be transformed into geometric inequality.

Since $$c^2=a^2+b^2-ab\implies c^2=a^2+b^2-2ab \cos60$$

We can think that $a,b,c$ are lengths of sides of a triangle such that the measure of the angle opposed to the side of length $c$ is 60 degrees.

The angles of the triangle $ABC$ satisfy $\angle A\ge60, \angle B\le60$ or $\angle B\ge60, \angle A\le60$.

Hence using the property (In a triangle, the longest side is opposite to greatest angle), we can say that $a\ge c \ge b$ or $a\le c \le b$.

In any case, it follows that $(a-b)(b-c)\le 0$.

$\endgroup$
3
  • 2
    $\begingroup$ Oh nice, never would've thought of that. $\endgroup$ Dec 30 '16 at 15:23
  • 2
    $\begingroup$ Thanks @SimpleArt, I know you are lying $\endgroup$ Dec 30 '16 at 15:27
  • $\begingroup$ @THELONEWOLF. Nice answer. +1 $\endgroup$ Dec 30 '16 at 16:11
7
$\begingroup$

The expression $ a^2 + b^2 - ab = c^2 $ is equivalent to $$ a^2 + b^2 - ab = c^2 \longleftrightarrow a^2 - ab = c^2 - b^2 \longleftrightarrow a(a - b) = (c - b)(c + b) $$ Now we multiply by $ b - c $ both sides (if $ b - c = 0 $ then there is nothing to prove): $$ a(a - b)(b - c) = (c - b)(c + b)(b - c) = -(c - b)^2 (c + b) $$ The right side is negative, because $ -(c - b)^2 \leq 0 \ $ (a square is always positive) and $ c,b \geq 0 \rightarrow c + b \geq 0 $. Then we deduce $$ a(a - b)(b - c) \leq 0 $$ And we know that $ a \geq 0 $, so $$ (a - b)(b - c) \leq 0 $$

$\endgroup$
3
$\begingroup$

We have $ a^2+b^2-ab=c^2$, then $ (a-b)^2=c^2-ab\ge 0$. So $ c^2\ge ab $. This implies that at least one of $ c\ge a $ or $ c\ge b $ is true.

First case: $ c\ge a $. Then $ b^2-ab=b (b-a)=c^2-a^2\ge 0$, so $ b\ge a $. Thus we have $b^2-c^2=ab-a^2=a (b-a)\ge 0$, so $ b\ge c $. Therefore $(a-b)(b-c)\le 0$.

Second case: $ c\ge b$. Then $ a^2-ab=a (a-b)=c^2-b^2\ge 0$, so $ a\ge b $. Hence $(a-b)(b-c)\le 0$.

$\endgroup$
1
  • 1
    $\begingroup$ nice approach, +1 $\endgroup$ Dec 30 '16 at 14:45
3
$\begingroup$

We need to prove that $$(a-b)\left(b-\sqrt{a^2+b^2-ab}\right)\leq0$$ or $$\frac{-a(a-b)^2}{b+\sqrt{a^2+b^2-ab}}\leq0$$ and we are done!

$\endgroup$
2
$\begingroup$

The condition is $$b^2+a(a-b)=c^2.$$ Now:

$\quad\bullet\quad$ If $a\geq b$ then $c^2\geq b^2\implies c\geq b$.

$\quad\bullet\quad$ If $a\leq b$ then $c^2\leq b^2\implies c\leq b$.

In both cases the result follows.

$\endgroup$
1
$\begingroup$

From given equality we have $c=\sqrt {a^2+b^2-ab}$, then you can plug this in your inequality and you get $(a-b)(b-\sqrt{a^2+b^2-ab})$, now you have 2 cases to look at:

First: $a>b, a=b+x$ with this your first term is positive, so we have to show second one is negative, thus we have $b-\sqrt{b^2+bx+x^2};\sqrt{b^2+bx+x^2} > \sqrt {b^2}$, it is obvious from here that the product is negative.

Second: $a<b,a=b-x$, now we know that first term is negative, so we have to show that second one is positive, again we plug in and get $b-\sqrt{b^2-bx-x^2};\sqrt{b^2-bx-x^2} < \sqrt {b^2}$, so we know that this one is positive, so the product is again negative.

And finally if $a=b$ then their product is $0$ because $a-b=0$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.